Building-integrated solar thermal system with/without phase change material: Life cycle assessment based on ReCiPe, USEtox and Ecological footprint. (20th August 2018) - Lamnatou, Chr.; Motte, F.; Notton, G.; Chemisana, D.; Cristofari, C.
Abstract: The present study assesses the environmental profile of a building-integrated solar thermal system that has been developed and tested in France. The investigation is based on life-cycle assessment according to ReCiPe, USEtox and Ecological footprint. Two configurations (for the solar collector) have been examined: 1) Without phase change material (using only rock wool as insulation) and 2) With phase change material (myristic acid) and rock wool. The main goal is the evaluation of the effect of the phase change material on the environmental profile of the solar thermal system. Both cases (with/without phase change material) have been studied based on the Mediterranean climatic conditions of Ajaccio (France). The results, according to ReCiPe midpoint (with characterization) demonstrate that the tubes (copper), the aluminium components (absorber, casing, gutter) and the phase change material are responsible for the highest impacts in terms of the material manufacturing phase of the collectors. With respect to ReCiPe/endpoint/single-score life-cycle results (scenarios: with/without PCM; with/without recycling; including the gutter), the values vary from 0.014 to 0.020 Pts/kWh. The configuration with phase change material presents 0.003 Pts/kWh higher impact (in comparison to the option without phase change material). Recycling offers an impact reduction of 0.003 Pts/kWh (for both configurations with/without phase change material). In addition, results according to USEtox (in terms of human toxicity and ecotoxicity) and Ecological footprint (with respect to the impact categories of carbon dioxide, nuclear and land occupation) are presented and discussed. Highlights: Life cycle assessment (LCA) of a building-integrated solar thermal (BIST) system. Configurations with/without phase change material (PCM) have been examined. Life-cycle ReCiPe/endpoint results: 0.014–0.020 Pts/kWh, depending on the scenario. Case with PCM: 0.003 Pts/kWh higher impact (in comparison to the case without PCM). Recycling: impact reduction of 0.003 Pts/kWh in both cases (with/without PCM).